Artisans Meet Design: the Reception of the Turkish Handicraft Development Office in Turkey - Emgin, Bahar; Emgin, Bahar (Oxford University Press, 2020)
Peter Muller-Munk Associates, an American industrial design firm, established the Turkish Handicraft Development Office in 1957 in Ankara as part of the US technical assistance program to developing nations. The aim of the program was to improve selected local crafts products in order to make them appealing for the American market. To this end, American designers and local craftspeople produced about 150 prototypes formed by creative combinations of meerschaum, copperware, ceramics, woodwork and basket weaving. When the office was closed in the early 1960s because of its failure to mass-produce the samples, it left behind a lively debate regarding the improvement of craft production and its relation to industrialization and economic growth. This article focuses on these debates to determine the place allocated to design within the discussions of crafts as a socio-economic activity. The article will focus on the reception of the design assistance program among the local actors to answer how Turkish crafts practitioners and officials perceived design, how the emergent concept of design was linked with handicraft and artisanal production, and how it took place as part of the agenda of economic and industrial development.
Keywords: Crafts; Design; Design history; Regional development